Physical and chemical characteristics of two wetlands in Lake Danao Natural Park, Ormoc City - Alfante, Nadia P.; Patindol, Teofanes A. (Annals of Tropical Research, 2005)
The study was conducted to characterize the wetlands located at Sitio Quinto Limbo and Tasakan in Lake Danao Natural Park, Ormoc City based on some physico-chemical parameters. The two wetlands are generally shallow. Salinity ranged from 0.3 to 0.5 ppt which is characteristic of an oligohaline wetland. Sediment and water were slightly acidic. Concentrations of ammonium ions were lower than the normal value. Levels of nitrate and phosphate ions exceeded the normal value of 1mg/L and 0.025 mg/L, respectively. Lead ion concentrations were generally within the normal range (10-100 mg/kg). Mean cadmium ion concentration was normal (0.01-1.0 mg/kg) although in some sites concentrations beyond the normal range were observed. Based on the findings, it is recommended that conservation program be urgently implemented in the study area to ensure the conservation of the wetlands and their resources.